[Thriving transitions in celebration of the College of Education Week 1998] - Abrenica, Alexa P. (Animo Repository, 1998)
Dr. Alexa Abrenica, Chair of the Psychology Department gave a talk on Thriving transitions in celebration of the College of Education Week 1998.